Interactions of dissolved CO2 with Cadmium Isotopes in the Southern Ocean - de,Baar HJW; van,Heuven SMAC; Abouchami,W; Xue,ZICHEN; Galer,SJG; Rehkamper,M; Middag,R; van,Ooijen J (Marine Chemistry, 2017)
Here we report the first ever observations of a strong correlation in ocean surface waters of the dissolved δ114Cd with dissolved CO2. This is observed in the Southern Ocean along the 0°W meridian in both the Antarctic Circumpolar Current and the Weddell Gyre, as well as in the Weddell Sea proper, near the Antarctic Peninsula and in Drake Passage. This uniform trend in several surface water masses hints at a uniform biochemical mechanism within the Southern Ocean. One hypothesis for the underlying mechanism would be a role of Cd in the carbonic anhydrase function for conversion of bicarbonate ion [HCO3−] into CO2, the latter being required by RuBisCO (ribulose-1,5-bisphosphate carboxylase/oxygenase) that only accepts CO2. At low ambient [CO2] the algae maintain growth by also operating a Carbon Concentrating Mechanism (CCM) for utilization of [HCO3−] and its conversion to CO2. For this the algae need more enzyme carbonic anhydrase that normally has Zn as its co-factor, but Cd may substitute for Zn and there also are Cd-specific carbonic anhydrases known for some phytoplankton species. Indeed in incubations of the local plankton communities it is shown that the phytoplankton have a very strong preferential uptake of CO2, such that the uptake ratio {[CO2]/[HCO3−]} is much higher than the dissolved ratio {[CO2]/[HCO3−]} in ambient seawater. Therefore the here reported observations in the Southern Ocean are also expressed for δ114Cd as function of the ratio {[CO2]/[HCO3−]} in ambient seawater. Future research of local phytoplankton in unperturbed natural waters of the Southern Ocean is recommended to be able to verify the hypothesis of a function of Cd in carbonic anhydrase in Antarctic phytoplankton.